2007
DOI: 10.1042/bst0350652
|View full text |Cite
|
Sign up to set email alerts
|

Matrix synthesis and degradation in human intervertebral disc degeneration

Abstract: Degeneration of the intervertebral disc has been implicated in chronic low back pain. Type II collagen and proteoglycan (predominantly aggrecan) content is crucial to proper disc function, particularly in the nucleus pulposus. In degeneration, synthesis of matrix molecules changes, leading to an increase in the synthesis of collagens type I and III and a decreased production of aggrecan. Linked to this is an increased expression of matrix-degrading molecules including MMPs (matrix metalloproteinases) and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
372
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(390 citation statements)
references
References 49 publications
9
372
2
7
Order By: Relevance
“…Overexpression of MMPs is clearly associated with both osteoarthritis and IVD degeneration [12]. In the current study, our microarray results indicated that NGF increases expression of a number of MMPs such as MMP3 and MMP13 consistent with previous investigations that have shown similar activity of NGF in other tissues and cell systems, including smooth muscle cells and pancreatic cancer cells [13,24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overexpression of MMPs is clearly associated with both osteoarthritis and IVD degeneration [12]. In the current study, our microarray results indicated that NGF increases expression of a number of MMPs such as MMP3 and MMP13 consistent with previous investigations that have shown similar activity of NGF in other tissues and cell systems, including smooth muscle cells and pancreatic cancer cells [13,24].…”
Section: Discussionsupporting
confidence: 91%
“…Matrix degradation as a result of over production of matrix metalloproteinases (MMPs) is a major component of the pathological processes that lead to IVD degeneration [12] and NGF has been shown to increase MMP expression in a number of tissues and cell systems [13]. Furthermore, NGF has been shown to induce neoangiogenesis in a range of normal and pathological conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed previously, elastic fibres contain molecules other than elastin, in particular fibrillins, which are the principal components of elastic microfibrils. Fibrillins are degraded by several members of the matrix metalloproteinase family [4]; in particular, these include MMPs-2, -3, and -13, which demonstrate increased presence in degenerate discs [36].…”
Section: Roles Of Elastic Fibres In the Ageing And Degeneration Of Thmentioning
confidence: 99%
“…It is characterized by structural failure and loss of IVD height due to proteolytic degradation of the extracellular matrix (1). Lower back pain in adult individuals is commonly associated with IVD degeneration (2).…”
mentioning
confidence: 99%